The Effect of Digital Literacy and Innovation Resistance to Use Digital Payment for Taxpayers - Ni Made Susi Adnyani; Ni Kadek Sinarwati; Fridayana Yudiatmaja (Faculty of Economics and Business Udayana University, 2023)
The growth of digital payments is accelerating with technological advancements, which must fully pique the interest of the general public, particularly the land and building taxpayers in Buleleng Regency. This study looks at how innovation resistance and digital literacy affect taxpayers' desire in adopting digital payments for land and buildings in the Buleleng area. Utilizing a questionnaire, this study is quantitative. 178 respondents were chosen using a chance sample technique from the population of this study, which consists of land and building taxpayers in the Buleleng regency. Using SEM-PLS analysis, test the data. According to the study's findings, digital literacy significantly and favorably influences people's intentions to utilize digital payments, (2) the desire to use digital payments is negatively and significantly impacted by innovation resistance, (3) the intention to use digital payments is impacted simultaneously by both digital literacy and innovation resistance. Keywords: Digital Literacy, Innovation Resistance, Behavior Intention, Digital Payment